An inquiry into the experiences of adolescents in multiple residential treatment settings: do perceptions change over time and at follow-up? - Heinrichs, Timothy Francis (1998)
The following is a qualitative study that examined the perceptions of adolescents who have been placed in residential treatment. Analyzed were respondents who were in treatment at the time of the interview, respondents who had been out of treatment for less than one year, and respondents out of treatment more than one year;The researcher was interested in whether adolescents' perceptions of placement changed following treatment, as well as over time. Further, respondents were asked whether the tenets of Labeling or Deterrence Theories applied to their experiences;Respondents in treatment at the time of the interview initially responded with complaints or dislikes of the program. As the interview went on, responses eventually becoming more positive as respondents were able to vent negative feelings;Respondents who had been out of treatment less than twelve months were more positive, sharing aspects of treatment they felt applied to their lives outside of treatment. Most respondents stated they learned new skills and discipline to cope, as well as increased feelings of self esteem;Respondents who had been out of treatment for more than one year presented positive aspects of their programs, but became more negative. These respondents felt they had learned skills in treatment, but the realities of life and short periods of after-care made it difficult for them to succeed;The majority of respondents in all three groups reported they had received negative labels. While some saw those labels as negative, wanting to change those negative labels as in the tenets of Deterrence Theory, most seemed to assume identities based on negative labels such as juvenile delinquent and criminal , as in Labeling Theory. Labels seemed to be more detrimental than challenging when used, regardless of the intention of the labeler;Residential treatment was reported as lacking consistent family therapy, as well sustained follow-up. One solution included providing community social services to the resident and family during the program, as well as for extended periods following residential treatment. If done this way the first time, we may alleviate extended or multiple residential treatment placements